From research to policy: Preventing residential burglary through a systems approach - Robinson, Matthew B. (American journal of criminal justice, 2000)
This paper isolates crime prevention policy implications which stem from a series of interrelated environmental studies of residential burglaries. A number of crime prevention strategies are developed using a systems approach. It is argued that changes made to the environments of individuals, groups, communities, organizations, and society can achieve lower risks of residential burglary victimization.